PERAN ISLAMIC SOCIAL REPORTING TERHADAP NILAI PERUSAHAAN - Sutapa Sutapa; Heri Laksito (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2018)
This study aimed to obtain empirical evidence about the influence of profitability and the disclosure ofIslamic Social Reporting (ISR) on firm value on Islamic banking in Indonesia. The population of this research is all of Islamic Bank in Indonesia 2014 - 2016. The sample of this research is Islamic Bank in Indonesia by using purposive sampling method. There are e l e v e n b a n k s and obtained 44 observations. Classic assumption test performed for data analysis and regression analysis to test the hypothesis. The results of this study indicate that Profitability significantly influence the level of Social Reporting Islam and corporate values, Islamic Social Reporting does not affect the value of the company While profitability has a significant effect on corporate value, while the ISR has no significant effect on the level of corporate value.